Oxytocin Massage Management To Facilitate Mother Postpartum breast milk in Pekanbaru City Murtinawita In PMB 2019: Oxytocin Massage Management To Facilitate Mother Postpartum breast milk in Pekanbaru City Murtinawita In PMB 2019 - Rika Andriyani (Journal of Midwifery and Nursing, 2020)
Postpartum Period (Peurperium) is the period that starts after the placenta comes out and ends when the means of content back to normal (before pregnancy). Sometimes in the puerperium there are complications or problems that occur in the breast-feeding for infants. Breastfeeding is a fun experience or be an unpleasant experience for both mother and baby. one of the problems in the process of breastfeeding is clogged milk and milk no problem spending smoothly. In this case the authors do midwifery care in puerperal women with oxytocin massage to smooth milk and also conduct thorough and continuous care through SOAP documentation approach. The case study method: This case using SOAP documentation approach. Making the case carried out by two visits. Midwifery care with massage oxytocin performed at Ny. A 24-year-old milk that is not smooth, after the midwifery care with massage 2 times in one day with a time of 2-3 minutes before breastfeeding then get results in the mother breastfed expenditure to be smooth. As the health service should in PMB Murtinawita form postpartum classes such as gymnastics parturition and teach massage oxytocin to mothers experiencing breastfeeding problems in the process so that the process of breastfeeding and exclusive breastfeeding can be achieved after the midwifery care with massage 2 times in one day with a time of 2-3 minutes before breastfeeding then get results in the mother breastfed expenditure to be smooth. As the health service should in PMB Murtinawita form postpartum classes such as gymnastics parturition and teach massage oxytocin to mothers experiencing breastfeeding problems in the process so that the process of breastfeeding and exclusive breastfeeding can be achieved after the midwifery care with massage 2 times in one day with a time of 2-3 minutes before breastfeeding then get results in the mother breastfed expenditure to be smooth. As the health service should in PMB Murtinawita form postpartum classes such as gymnastics parturition and teach massage oxytocin to mothers experiencing breastfeeding problems in the process so that the process of breastfeeding and exclusive breastfeeding can be achieved